The Effectiveness of Sponsorship Program Analysis at the Persip Football Club in Building Brand Awareness of Pekalongan University - Danang Satrio; Ayuningrum, Anggrainy Putri; Pambudianing, Nadya (Indonesian Journal of Sport Management, 2024)
Sponsorship is showing tremendous growth and is becoming a popular marketing communication to increase brand awareness. The purpose of this study is to analyze how the sponsorship carried out by Pekalongan University can affect UNIKAL brand awareness itself. This research was conducted on the sponsor of a leading football club in the city of Pekalongan which became the champion of the Central Java league 3 twice in a row, namely PERSIP. The research was conducted in a qualitative way using PLS-SEM for simple regression. This research has a Technology Uptake Rate of 3. The results of sponsorship research on PERSIP football clubs are an effective strategy in building unique and strong brand awareness among football fans. This success is supported by the loyalty and strong identification of fans towards the sponsoring brand, which in turn strengthens the brand image and increases consumer loyalty to the products or services offered by the sponsoring company.